Experiences of restrictiveness in forensic psychiatric care: systematic review and concept analysis - Tomlin, Jack; Bartlett, Peter; Völlm, Birgit (Elsevier, 2018)
Mentally disordered offenders may be sent to secure psychiatric hospitals. These settings can resemble carceral spaces, employing high levels of security restricting resident autonomy, expression and social interaction. However, research exploring the restrictiveness of forensic settings is sparse. A systematic review was therefore undertaken to conceptualize this restrictiveness. Eight databases were searched for papers that address restrictive elements of secure forensic care in a non-cursory way. Fifty sources (empirical articles and policy documents) were included and subject to thematic analysis to identify 1) antecedent conditions to, 2) characteristic attributes, 3) consequences and 4) ‘deviant’ cases of the developing concept.